Лемещук Л. В. Текст у світлі новітніх теорій пізнання - Лемещук Л. В. (Philological Treatises, 2020)
The article is devoted to the text and its peculiarities that form its logical and semantic structure and are distinguished as textual categories in linguistic literature. The text is defined as a means of accumulating and transmitting information. The text structure is considered as a dynamic unity of its elements and substructures is characterized as an integral communicative system.